Learn to code with Rust - Paskhaver, Boris (Packt Publishing, 2024)
This course begins by guiding you through the essential setup process, helping you configure your environment on macOS or Windows, and crafting your first Rust project. From there, you'll master variables, data types, and control flow, ensuring a solid understanding of Rust's syntax and semantics. As you progress, explore Rust's innovative concepts like ownership, borrowing, and lifetimes. These principles, combined with lessons on enums, generics, and error handling, will enhance your ability to write efficient, bug-free code. Delve into Rust's memory safety guarantees without sacrificing performance, learning to leverage features like the Option and Result enums for error management. Finally, unlock Rust's advanced capabilities by building modules, working with traits, and understanding lifetimes. Gain the confidence to design scalable and maintainable projects, culminating in a robust understanding of the language. With clear explanations and hands-on exercises, this course ensures you are well-equipped to thrive in Rust's growing ecosystem.
Online resource; title from title details screen (O'Reilly, viewed December 2, 2024)
Keywords: Rust (Computer program language); Computer software -- Development; Software engineering; Rust (Langage de programmation); Génie logiciel; Instructional films; Nonfiction films; Internet videos; Films de formation; Films autres que de fiction; Vidéos sur Internet